A modified biodegradable mesh ureteral stent for treating ureteral stricture disease. (1st January 2023) - Wang, Yichun; Ren, Xiaohan; Ji, Chengjian; Zhong, Da; Wei, Xiyi; Zhu, Zheng; Zhou, Xuan; Zhang, Xi; Wang, Shuai; Qin, Chao; Song, Ninghong
Abstract: Ureteral stricture disease (USD) is a common urologic condition. Patients with ureteral stricture disease may suffer from ipsilateral flank pain, nausea, urinary calculi, infection, and impaired renal function. The treatments of USD include surgery, followed by implantation of the ureteral stent to aid the drainage of the urine. The traditional ureteral stent may sometimes cause urological infection, encrustation, and discomfort. To decrease the complication of the ureteral stent, we modified the structure and material based on the traditional ureteral stent. The traditional nondegradable Double-J shape tubular ureteral stent was turned into the biodegradable mesh ureteral stent. The modified mesh ureteral stent and Double-J ureteral stent were inserted into the ureters of the USD animals, respectively. The results of the gross morphology, serology, urinalysis, histology, microstructure, et al. demonstrated that modified mesh ureteral stent has a favorable ability in supporting the ureter and has no effect on cell proliferation, migration, apoptosis, and cell cycle of the human uroepithelial cells. The mesh ureteral stent could relieve ureter obstruction and can be slowly biodegraded after 3-5 months of implantation without the need for a second surgery to remove the stent. Compared to the Double-J ureteral stent, the modified mesh ureteral stent has a lower rate of urinary tract infection and less encrustation. It is expected to be an alternative treatment approach for USD. However, due to the limited number of animals and clinical data, further study focused on the application value in clinical practice are essential. Statement of significance: This study demonstrates: 1. A modified biodegradable mesh ureteral stent; 2. Without the need for a second surgery to remove the stent; 3. A lower rate of urinary tract infection and less encrustation than a double-J ureteral stent; 4. An alternative treatment approach for USD. Graphical abstract: Image, graphical abstract